Penolakan Harta Warisan Oleh Ahli Waris Perspektif Hukum Islam dan KUH Perdata - Zubair, Asni; Arfhan, Muhammad; Leleang, Andi Tenri (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research discusses the legal implications of the rejection of inherited property in the perspective of Islamic law and the Indonesian civil law system (Civil Code). In Islamic law, the rejection of inherited property is understood as the resignation of an heir or several heirs from their right to receive a share of the inheritance, provided that it can be accompanied by the provision of compensation either from the inherited property itself or from other heirs, as stipulated in Article 183 of the Compilation of Islamic Law (KHI). Meanwhile, in the Civil Code Article 1057-1058, the refusal is made expressly through an official statement before the Registrar of the District Court in the jurisdiction where the inheritance is open. This research uses a normative juridical method with a comparative approach to analyze the doctrines of classical Islamic inheritance law and the provisions of positive Indonesian legislation. The results show that in Islamic law, rejection does not erase the status of heirs, but only serves as a voluntary relinquishment of rights. In contrast, in the civil law system, rejection causes a person to be considered never to be an heir so that all rights and obligations, including the obligation to pay off the testator's debt, are canceled. This difference indicates a difference in legal philosophy: Islamic law emphasizes family management and balance of justice between heirs, while civil law emphasizes procedural certainty and protection of third parties, especially creditors. This study emphasizes the importance of harmonizing the principles of the two legal systems within the framework of Indonesia's pluralistic inheritance law to prevent inheritance disputes.